Photoperiod length paces the temporal orchestration of cell cycle and carbon‐nitrogen metabolism in Crocosphaera watsonii. (10th July 2013) - Dron, Anthony; Rabouille, Sophie; Claquin, Pascal; Talec, Amélie; Raimbault, Virginie; Sciandra, Antoine; Vicente, Miguel; Ayala, Juan; Daley, Daniel
Summary We analysed the effect of photoperiod length (PPL) (16:8 and 8:16 h of light–dark regime, named long and short PPL, respectively) on the temporal orchestration of the two antagonistic, carbon and nitrogen acquisitions in the unicellular, diazotrophic cyanobacterium Crocosphaera watsonii strain WH8501 growing diazotrophically. Carbon and nitrogen metabolism were monitored at high frequency, and their patterns were compared with the cell cycle progression. The oxygen‐sensitive N2 fixation process occurred mainly during the dark period, where photosynthesis cannot take place, inducing a light–dark cycle of cellular C : N ratio. Examination of circadian patterns in the cell cycle revealed that cell division occurred during the midlight period, (8 h and 4 h into the light in the long and short PPL conditions, respectively), thus timely separated from the energy‐intensive diazotrophic process. Results consistently show a nearly 5 h time lag between the end of cell division and the onset of N2 fixation. Shorter PPLs affected DNA compaction of C. watsonii cells and also led to a decrease in the cell division rate. Therefore, PPL paces the growth of C. watsonii: a long PPL enhances cell division while a short PPL favours somatic growth (biomass production) with higher carbon and nitrogen cell contents.